The Theoretical Linkages between the Shariah Supervisory Board (SSB) and Stakeholder Theory in the Islamic Financial Institutes: An Empirical Review - Islam, K. M. Anwarul; Bhuiyan, Abul Bashar (International Journal of Accounting & Finance Review, 2019)
As part the Corporate Governance, the Shariah Supervisory Board has a significant role in the Islamic Financial Institutes for ensuring its conformity with the Shariah standards. In general, the Corporate governance should be played essential roles to design and promote principles of fairness, accountability, and transparency to meet of all the stakeholder’s rights such as shareholders, the workers, the depositors, and the customers, etc. however, there are still struggling for convincing arguments to justify stakeholders’ participation in governance in the traditional conventional systems rather, the Stakeholder theory has become one of the most important developments in the field of business ethics, which is widely regarded as being a key element in Islamic banking, making it of extreme relevance in Islam’s principles of property rights, commitment. Therefore, this study aims to justify the theoretical linkages or relationship between the role of the Shariah Supervisory Board of Islamic banking and stakeholders’ model from the existing empirical literature review. The summary of empirical review findings revealed that the stakeholder concept in a way that overcomes many of the existing limitations and provides a different understanding of the identity and meaning of Islamic banking, specifically in terms of its relationship to stakeholder groups, such as Islamic banks are a connected body, they should have control over the external environment and should implement hierarchies. Moreover, the developed a conceptual framework to do empirical research by applying real data to test the significance of the above relationships for further policy explorations.